Nutritional Value and Utilization of Yams (Dioscorea steriscus) by Residents of Bindura Town High Density Suburbs, Zimbabwe - S. Washaya; J. F. Mupangwa; E. Muranda (Advances in Agriculture)
The objective of this study was to assess utilization levels, availability, nutritional value, and magnitude of sales by vendors of Dioscorea steriscus by residents of Bindura. A multistage sampling procedure was used to select respondents. Data were subjected to Chi-square, logistic regression, and correlation to determine the effects of demographic determinants on utilization of D. steriscus. Questionnaires were used to collect data. Results show that education status and period of stay significantly affect the consumption of D. steriscus (P<0.05). It was also observed that consumption is frequent between lunch and supper (47%) compared to breakfast. D. steriscus has high iron (6.8%), ash (2.06%), and CF (16.8%) contents but it is low in protein (0.83%). Irrespective of gender of respondent, suburb of residence, size of family, period of stay, education level, employment status, and source of income, respondents will grow D. steriscus for use as food supplement (odds ratio = 0.475). The period of stay (r=0.08) and education level (r=0.08) positively affect the growing of D. steriscus. D. steriscus can be used as source of energy and can also be used possibly for medicinal purposes. Further study is required on possibility of phytochemicals and cytotoxic components to justify its use.